How operations matters in healthcare standardization. Issue 9 (25th September 2019) - De Regge, Melissa; Gemmel, Paul; Meijboom, Bert
Abstract : Purpose: Process management approaches all pursue standardization, of which evidence-based medicine (EBM) is the most common form in healthcare. While EBM addresses improvement in clinical performance, it is unclear whether EBM also enhances operational performance. Conversely, operational process standardization (OPS) does not necessarily yield better clinical performance. The authors have therefore looked at the relationship between clinical practise standardization (CPS) and OPS and the way in which they jointly affect operational performance. The paper aims to discuss this issue. Design/methodology/approach: The authors conducted a comparative case study analysis of a cataract surgery treatment at five Belgium hospital sites. Data collection involved 218 h of observations of 274 cataract surgeries. Both qualitative and quantitative methods were used. Findings: Findings suggest that CPS does not automatically lead to improved resource or throughput efficiency. This can be explained by the low level of OPS across the five units, notwithstanding CPS. The results indicate that a wide range of variables on different levels (patient, physician and organization) affect OPS. Research limitations/implications: Considering one type of care treatment in which clinical outcome variations are small complicates translating the findings to unstructured and complex care treatments. Originality/value: With the introduction of OPS as a complementary view of CPS, the study clearly shows the potential of OPS to support CPS in practice. Operations matters in healthcare standardization, but only when it is managed in a deliberate way on a hospital and policy level.